WhatsApp groups: The nexus between retention, reciprocity, and user satisfaction - Ali, Ismail Mohamed; Mohamed, Mohamud Ahmed; Ahmed, Yahye Abukar (Frontiers in Education, 2024)
High dropout rates in higher education pose a significant challenge, prompting a need for effective retention strategies. Research shows promoting students' engagement as key factor in retention. This is most effectively nurtured through regular activities that explicitly connect to academic goals and involve all students. This study proposes to investigate the role of reciprocity which involves the exchange of knowledge and resources on the basis of mutual benefits, and considers WhatsApp groups as an interactive medium for connecting and sharing. Data from an online questionnaire of 309 university students was used to test the research model. Data analysis was performed using the partial least squares method. The findings revealed that that information quality (IQ) and service quality (SERQ) exert a positive influence on satisfaction (SAT), while system quality (SQ) does not. Similarly, reciprocity has a positive influence on both SAT and intention to stay (INTENT). Moreover, our study reaffirmed the established positive relationship between SAT and INTENT. Online platforms like WhatsApp groups, supported by reciprocity and a higher quality of contents and services, can promote satisfaction and knowledge sharing among students, ultimately addressing the challenge of student retention in higher education.